Analisis Pengaruh Budaya Organisasi dan Keadilan Organisasi Terhadap Organizational Citizenship Behavior (OCB) Dengan Komitmen Organisasional Sebagai Variabel Intervening - Humairo, Alya Dahana; Suryatni, Mukmin (Postgraduate, University of Mataram, 2024)
This study aims to determine the Analysis of the Influence of Organizational Culture and Organizational Justice on Organizational Citizenship Behavior (OCB) with Organizational Commitment as an Intervening Variable. (Study on Employees of the Mataram City Health Office). This study used primary and secondary data obtained through the distribution of questionnaires to respondents who were employees of the Mataram City Health Office. The population in this study is 76 employees of the Mataram City Health Office. This research is a quantitative research. The analysis method uses Partial Least Squares Structural Equation Modeling (PLS-SEM) using the SmartPLS v.4.0 tool. The results of the study show that Organizational Culture has a significant positive effect on Organizational Citizenship Behavior (OCB), Organizational Justice has a positive and significant effect on Organizational Citizenship Behavior (OCB), Organizational Culture has a positive and significant effect on Organizational Commitment, Organizational Justice has a positive and significant effect on Organizational Commitment, Organizational Commitment has a positive and significant effect on Organizational Citizenship Behavior (OCB), Organizational Culture has a positive and significant effect on Organizational Commitment through Organizational Citizenship Behavior (OCB), Organizational Justice has a positive and significant effect on Organizational Commitment through Organizational Citizenship Behavior (OCB).